2016
DOI: 10.1038/ncomms10771
|View full text |Cite
|
Sign up to set email alerts
|

A highly active and stable hydrogen evolution catalyst based on pyrite-structured cobalt phosphosulfide

Abstract: Rational design and controlled synthesis of hybrid structures comprising multiple components with distinctive functionalities are an intriguing and challenging approach to materials development for important energy applications like electrocatalytic hydrogen production, where there is a great need for cost effective, active and durable catalyst materials to replace the precious platinum. Here we report a structure design and sequential synthesis of a highly active and stable hydrogen evolution electrocatalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
316
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(356 citation statements)
references
References 52 publications
26
316
0
1
Order By: Relevance
“…The S 2p spectrum showed two core level peaks at 162.7/163.9 eV in the lower binding energy region and another two peaks at 168.6/169.7 eV in the higher binding energy region. [29] For the P 2p spectrum, a small peak at 129.5 eV represented Co-P binding, [29,30] while two peaks at 133.7 and 134.6 eV were attributed to partial surface oxidation in Co x P resulting from exposure to air. [40] In particular, the two peaks at 168.7 eV in the S 2p spectrum were related to the existence of sulfate in (Co 1−x Ni x )S 2 /G, indicating that (Co 1−x Ni x )S 2 /G is prone to oxidation upon a short exposure to air.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S 2p spectrum showed two core level peaks at 162.7/163.9 eV in the lower binding energy region and another two peaks at 168.6/169.7 eV in the higher binding energy region. [29] For the P 2p spectrum, a small peak at 129.5 eV represented Co-P binding, [29,30] while two peaks at 133.7 and 134.6 eV were attributed to partial surface oxidation in Co x P resulting from exposure to air. [40] In particular, the two peaks at 168.7 eV in the S 2p spectrum were related to the existence of sulfate in (Co 1−x Ni x )S 2 /G, indicating that (Co 1−x Ni x )S 2 /G is prone to oxidation upon a short exposure to air.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is uneconomical to produce a monofunctional electrocatalyst for each HER and OER, as this raises the manufacturing cost. [2,[29][30][31] Owing to the analogous ionic radius and crystal structure, transition metals (such as Ni and Fe) and P can be substituted in cation and anion sites, respectively. [9][10][11] Recently, transition-metal hydroxides, [7,12] phosphides, [8,[13][14][15][16] nitrides, [17,18] and chalcogenides [19][20][21][22] have been investigated as promising candidates for bifunctional electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Co 9 S 8 and a P dopant in carbon structures have been proven to be active species to create catalytic active sites for improving catalysts' activities. 40,41 In elemental mapping analysis, the element N was not detected, possibly owing to its low doping content in Co 9 S 8 @NPC-10, which can be further conrmed by the following high resolution XPS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Jaramillo et al 147 and Liu et al 148 Please do not adjust margins Please do not adjust margins showed an obviously enhanced performance for HER. For example, doping with other element, hybrid with other catalytic materials and composite with carbon materials were investigated.…”
Section: Transition Metal Phosphidesmentioning
confidence: 97%